2008
DOI: 10.1136/hrt.2007.132662
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of aortic valve regurgitation and outcome after percutaneous closure of atrial septal defects and patent foramen ovale

Abstract: AR occurred in 9% of patients with closed ASD and in 10% of patients with closed PFO. Indication for closure should consider this potential complication despite an otherwise safe interventional procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 18 publications
0
47
5
Order By: Relevance
“…Moreover we did not observe late adverse events. Although rare, late complications like conduction abnormality, endocarditis, thrombo-embolism or aortic valve regurgitation have been occasionally described (38)(39)(40). Device related aortic erosion remains a dreaded complication occurring in 0.5% in the literature (40).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover we did not observe late adverse events. Although rare, late complications like conduction abnormality, endocarditis, thrombo-embolism or aortic valve regurgitation have been occasionally described (38)(39)(40). Device related aortic erosion remains a dreaded complication occurring in 0.5% in the literature (40).…”
Section: Discussionmentioning
confidence: 99%
“…Viewed in the context of a recent article by Schoen et al in Heart, however, they are noteworthy. 2 Accordingly, to appreciate the study by Wöhrle et al fully, it should be read as a counterpoint to the report by Schoen et al, which was a surprise to many in its description of new or increased AR in 10% of 170 patients who underwent transcatheter closure of a PFO and 9% of 70 in whom a device was placed to close an atrial septal defect. 2 …”
mentioning
confidence: 79%
“…Schoen et al rationalized the delayed and progressive appearance of AR in their cohort by proposing that it was not the device per se that altered aortic valve function and caused AR but tissue overgrowth of the device exerting traction on the noncoronary sinus and leaflet. 2 Given that evaluation of explanted septal occlusion devices confirms a progressive biological response to the foreign body, with an initial deposition of fibrin and blood cells followed by fibroblastic ingrowth and organization, as well as a mild chronic inflammatory response, 7 the hypothetical cause of AR proposed by Schoen et al is plausible. However, it seems just as likely that any distortion of the aortic root or valve is more closely related to the device.…”
Section: Article See P 3002mentioning
confidence: 99%
“…21 None of the patients experienced worsened associated mitral valve regurgitation or tricuspid valve regurgitation, and none developed left ventricular failure after device closure of the ASD. 22, 23 A total of 16 patients experienced new-onset migraines, which diminished within several months in most patients, but 10 patients received additional ticlopidine.…”
Section: Resultsmentioning
confidence: 99%
“…Shoen et al reported that aortic regurgitation occurred in 9% of patients with closed ASD and in 10% of patients with closed PFO among 240 consecutive patients who underwent percutaneous closure. 21 The sprayed device of both disks over the aortic root could compress the non-coronary cusp after interatrial septum shrinkage developed because of endothelialization and tissue overgrowth on the device. When the balloon's stretched diameter was used to select the size of device, the increased device-to-defect ratio correlated with development of aortic regurgitation.…”
Section: Discussionmentioning
confidence: 99%